1986
DOI: 10.1029/gl013i001p00072
|View full text |Cite
|
Sign up to set email alerts
|

Eastward propagation of a plasma convection enhancement following a southward turning of the interplanetary magnetic field

Abstract: On October 27th 1984, high‐latitude ionospheric convection was observed by the European incoherent scatter (EISCAT) radar. For a nine‐hour period, simultaneous observations of the interplanetary magnetic field (IMF) were obtained sunward of the Earth's bow shock. During this period, the IMF abruptly turned southward, having previously been predominantly northward for approximately three hours, and a strong enhancement in convection was observed 11 ± 1 minutes later. Using the very high time resolution of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
61
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 11 publications
14
61
0
Order By: Relevance
“…These speeds are consistent with previously observed propagation speeds outside the merging gap (e.g. Lockwood et al, 1986;Saunders et al, 1992), and this supports our interpretation of the Halley-Sanae time delay.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These speeds are consistent with previously observed propagation speeds outside the merging gap (e.g. Lockwood et al, 1986;Saunders et al, 1992), and this supports our interpretation of the Halley-Sanae time delay.…”
Section: Discussionsupporting
confidence: 93%
“…Observations suggest that the speed of this tailward expansion is between 1 and 10 kms À1 depending on the magnetic local time of observation (e.g. Lockwood et al, 1986;Todd et al, 1986;Etemadi et al, 1988;Saunders et al, 1992). However, the speed of the global ionospheric response to IMF changes is a matter of current debate.…”
Section: Introductionmentioning
confidence: 99%
“…The antisunward propagation of a change in the ionospheric convection electric field was first reported by Lockwood et al (1986), who used the EISCAT (European Incoherent Scatter) radar to observe the consequent increase in F-region ion temperatures following a southwardturning of the IMF, as seen just outside the bow shock by the AMPTE (Active Magnetospheric Particle Tracer Explorer) spacecraft. This heating is caused by collisions between the convecting ions and neutral thermospheric atoms whose motion cannot respond as rapidly.…”
Section: Observations Of Ionospheric Convection Responses To Reconnecmentioning
confidence: 99%
“…The first two panels are characterized by the relatively weak convection (U PC * 15 kV) that prevailed through a long preceding period of northward IMF. The convection Early models and observations suggested that global convection reconfigured in response to IMF variations on timescales of tens of minutes, and that the onset of a response was delayed by increasing amounts away from the noon sector (Lockwood et al 1986;Todd et al 1988;Saunders et al 1992). A similar scenario was observed in SuperDARN flow velocity data by Taylor et al (1998) in response to a northward turning of the IMF; sunward flows appeared almost immediately in the noon sector (within *2 mins) following the northward turning, but the flow within the radar fields-of-view took *20 mins to completely reconfigure.…”
Section: The Dynamics Of Global Convectionmentioning
confidence: 99%